Stunting in Coastal Communities in Indonesia: A Review - Febriana Muchtar; Efi Srinugraha; Chintya Mulya La Ode Hibali (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Stunting remains a major public health issue in many coastal communities, driven by multiple factors including inadequate nutritional intake, limited maternal knowledge regarding healthy dietary practices, and restricted access to healthcare services. Objective: This study aims to review the risk factors, prevalence, and prevention strategies related to stunting in coastal areas based on findings from 20 research journal articles. Methods: A systematic literature review was conducted by analyzing 20 Indonesian-language journal articles that focus on stunting in coastal communities. The selected studies explore contributing factors, prevalence rates, and the effectiveness of various intervention strategies. Results: The review indicates that the primary causes of stunting include insufficient nutritional intake, low levels of maternal education, poor access to healthcare services, and inadequate sanitation. Effective interventions identified in the literature include nutrition education programs, the promotion of locally available nutritious foods, and the empowerment of community health workers such as posyandu (integrated health service post) cadres. Conclusion: To reduce the prevalence of stunting in coastal communities, community-based interventions are essential. These should focus on improving maternal and child nutrition, enhancing public health education, and increasing access to quality healthcare facilities. Keywords: Stunting, Coastal Communities, Nutrition, Local Food, Health Interventions.